2018
DOI: 10.5435/jaaos-d-16-00257
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Ultrasonography in the Shoulder and Elbow

Abstract: In the past 30 years, the use of ultrasonography in the field of orthopaedics has evolved. As ultrasonography has been refined, smaller machines with higher fidelity and better transducers have become available at a lower cost. Diagnostic and therapeutic applications of ultrasonography in the shoulder and elbow have expanded imaging options and provided alternatives to surgical management. Ultrasonography is a dynamic tool that affords immediate diagnostic assessment for clinical correlation and can be used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Recently, higher-frequency probes and smaller machines have been developed that have allowed for much better accuracy in diagnosis and in-office use by orthopedic surgeons 12, 27. Advancements in the equipment along with improvements in technique have allowed ultrasound to achieve accuracy equal to magnetic resonance imaging (MRI) in the diagnosis of both full-thickness and partial-thickness rotator cuff tears at a much lower cost 5, 19…”
mentioning
confidence: 99%
“…Recently, higher-frequency probes and smaller machines have been developed that have allowed for much better accuracy in diagnosis and in-office use by orthopedic surgeons 12, 27. Advancements in the equipment along with improvements in technique have allowed ultrasound to achieve accuracy equal to magnetic resonance imaging (MRI) in the diagnosis of both full-thickness and partial-thickness rotator cuff tears at a much lower cost 5, 19…”
mentioning
confidence: 99%
“…Despite the hesitancy for orthopaedic surgeons to use ultrasound, studies have repeatedly shown that orthopaedic surgeons are capable of diagnosing musculoskeletal injuries with ultrasound after a teaching workshop. 12,13 Orthopaedists have the distinct advantage of surgical experience lending to a deeper understanding of the relevant anatomy that makes ultrasound a useful tool to evaluate for injuries noninvasively.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for surgeons to rapidly gain US proficiency in the diagnosis of rotator cuff tears has also led to an increased push to include US training in orthopaedic residency programs. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The potential for surgeons to rapidly gain US proficiency in the diagnosis of rotator cuff tears has also led to an increased push to include US training in orthopaedic residency programs. 27 Five studies evaluated in this review included US and MRI diagnostic outcome data with arthroscopy as reference. 2,10,15,47,50 After meta-analysis, no significant differences were found in US and MRI diagnostic sensitivity, specificity, and accuracy for any sized-thickness, fullthickness, or partial-thickness supraspinatus tears (Figure 4).…”
Section: Discussionmentioning
confidence: 99%